Using the Learning Cycle 5e Model to Improve Student Activity and Outcomes in Relationship and Function Materials at SMA Negeri 1 Indramayu Class X Mipa 8 - Sekar Ananda Nata Tiara Ilmi; Denni Ismunandar; Runisah Runisah; Asep Maolana Akbar (International Journal of Science Education and Cultural Studies, 2023)
This study aims to determine the increase in activeness and student learning outcomes in the subject matter of relations and functions using the Learning Cycle 5e model. This research is a Classroom Action Research (CAR) conducted at SMA Negeri 1 Indramayu. The subjects in this study were students of class X MIPA 8, totaling 36 students. The instrument used in this study was the student observation sheet which aims to measure activeness while the formative tests given each cycle aim to measure the improvement of students' mathematics learning outcomes using the 5e learning cycle model. Based on the results of research and data analysis, the following results were found: cycle I could improve students' mathematics learning outcomes, namely out of 36 students, 27 students achieved learning completeness with a class average of 79.97 or above KKM, namely 75 with high mastery criteria and student activity that is equal to 91.66% of the target of 75%. Cycle II saw an increase in students' mathematics learning outcomes, namely out of 36 students, 36 students achieved learning completeness with a class average of 89.94 or above the KKM, namely 75 with very high completeness criteria and student activity, namely 100% of the 75% target.